Respuesta :
Given expression 3² × 3⁻⁵
We will apply the power rule [tex]x^m*x^n=x^{m+n}[/tex]
3² × 3⁻⁵ = 3²⁺⁽⁻⁵⁾ = 3²⁻⁵ = 3⁻³
We will then apply the power rule [tex]x^{-n} = \frac{1}{x^n} [/tex]
3⁻³ = [tex] \frac{1}{3^3} [/tex]
Final answer: [tex] \frac{1}{3^3} [/tex]
We will apply the power rule [tex]x^m*x^n=x^{m+n}[/tex]
3² × 3⁻⁵ = 3²⁺⁽⁻⁵⁾ = 3²⁻⁵ = 3⁻³
We will then apply the power rule [tex]x^{-n} = \frac{1}{x^n} [/tex]
3⁻³ = [tex] \frac{1}{3^3} [/tex]
Final answer: [tex] \frac{1}{3^3} [/tex]
Answer:
1/3 to the third power
Step-by-step explanation:
ok